The relationship of demographic factors and percieved leadership styles of leaders of students' societies in UiTM / Jalilah Ahmad, Rohana Sham and Leylawati Joremi - Ahmad, Jalilah; Sham, Rohana; Joremi, Leylawati (2010)
Several studies have identified and determined factors contributing to the preferred leadership styles of leaders in various types of organizations. Yet there are many other studies looking into the impact of those styles on subordinates and organizational performance. The theory of transformational and transactional leadership is by far one of the most comprehensive theories. The transactional-transformational leadership continuum developed by Avolio and Bass has been well studied and researched the world over, with enlightening findings. The Multifactor Leadership Questionnaire 45 item (MLQ Form 5X) has been employed to gauge the leadership styles of leaders of students' societies in Universiti Teknologi MARA. A total of 54 leaders and at least 3 of their committee members from societies representing academic programs and societies at the residential colleges participated, making a total of 267 respondents. Committee members were chosen as raters as they would be most familiar with the leadership behaviors of the presidents or vice presidents. This study focused on examining the relationships between the various demographic factors namely; parents' academic qualification and type of occupation, household income, the vicinity of homes from the towns or city centers and academic achievements, not only at the university but also at the SPM level, specifically the subjects of Mathematics, English and History and finally the choice of academic discipline represented by the academic clusters and the perceived preferred leadership styles of the leaders. Results revealed that though the leaders were more transformational (M=2.63) than transactional (M=2.32) but the leaders also displayed a fair share of the laissez-faire style (M=2.03). The study also revealed that there appear to be a statistically significant relationship between factors of the perceived leadership styles and students' achievements in History and English at the SPM level. These findings can form the basis for future research on these relationships and strategic actions to promote the development of competitive leaders.